Left atrial myxoma at 9 year-old child: Case report - Uysal, Ayhan; Burma, Oktay; Özgüler, Ibrahim Murat; Akın, Mehmet Mustafa (Logos Medical Publishing, 2013)
The incidence of primary cardiac tumors is 0.05 %, and atrial myxomas constitute more than 50 % of them. However, primary cardiac tumors of infants and children are rarely seen. The left atrial mass, detected in echocardiography performed during the monitorization of a 9-year-old child in pediatric clinic due to growth retardation, shortness of breath on exertion and tachypnea,was removed surgically. The pathological examination of the mass was identified as myxoma. We conclude that, these benign cardiac masses can confront us with severe symptoms particularly in the pediatric age group and the surgery can be done after rapid, and reliable establishment of diagnosis under echocardiographic control. © Cocuk Cerrahisi Dergisi. All rights reserved.
Dokuz yaşında çocukta sol atriyal miksoma: Olgu sunumu
Keywords: Atrial; Child; Myxoma; Surgery